Quantitative Analysis of Pharmaceutical Tablets Using LIBS-Technique. And compare the results with (PCA) analysis - Naser Almsellati (Surman Journal of Science and Technology, 2020)
Laser-induced breakdown spectroscopy (LIBS) is a type of atomic emission spectroscopy which uses a highly energetic laser pulse as the excitation source. In principle, LIBS can analyze any matter regardless of its physical state, be it solid, liquid or gas. LIBS may be used to evaluate the relative abundance of each constituent element, or to monitor the presence of impurities. Our experiments reveal that in addition to the presence of carbon, hydrogen, nitrogen and oxygen, which can be primarily attributed to the active pharmaceutical ingredients, specific inorganic atoms were also present in all the tablets. Initial attempts at classification by a ratio metric approach using oxygen (777 nm) to nitrogen (742.36 nm, 744.23 nm and 746.83 nm) compositional values yielded an optimal value at 746.83 nm to provide an acceptable classification.